Psalmenrezeption in der Passionsgeschichte des Matthäusevangeliums: eine intertextuelle Studie zur Verwendung, theologischen Relevanz und strukturgebenden Funktion der Psalmen in Mt 26-27 im Lichte frühjüdischer Psalmenrekurse - Euler, Alida C. (Wissenschaftliche Untersuchungen zum Neuen Testament, 2022)
In his passion narrative, Matthew draws on Psalms while presenting the events situated in Gethsemani, before the high council and Pilate, and during the crucifixion. Alida C. Euler carves out these heterogeneous references, charts them within the reception of Psalms within Matthew's Gospel as a whole and contextualizes them as part of the Early Jewish reception of Psalms.